Chapter 9. Leafy Vegetable Production: VPH ch. 9, CV293/HS728, rev. 6/2022 - Sandoya-Miranda, Germán; Kanissery, Ramdas; Dufault, Nicholas S.; Desaeger, Johan; Mészáros, Anna; Beuzelin, Julien (EDIS, 2022)
Chapter 9 of the Vegetable Production Handbook.